Local residents awareness towards the issue of mangrove degradation in Kuala Selangor, Malaysia - Abd Rahman, Mazni Adibah; Asmawi, M. Zainora (2015)
Mangroves in Malaysia reside on the coastlines, and the largest areas of mangrove are in the Northern Sabah. They are frequently concentrated on the sheltered shores of the west coast. Over four decades since 1980, mangroves are recorded to be declining due to several reasons. Aquaculture practices implemented in the first decade, which spreads faster in Peninsular Malaysia was the reason of mangrove depleting during the years. Therefore, it is the argument of this research that there is not enough awareness of several stakeholders, making it less responsible for taking care of the mangrove forest.